Polycarbonate/clay nanocomposites via in situ melt polycondensation - Rama, Mallikarjuna S.; Swaminathan, Sivaram (Industrial & Engineering Chemistry Research, 2010)
Polycarbonate (PC)/clay nanocomposites were prepared via in situ melt polycondensation using novel organoclays modified using phosphonium and imidazolium based cations. The molecular weight of the separated polymer separated from the nanocomposites reveals that phosphonium ion modified organoclays catalyze the polycondensation of bisphenol A with diphenyl carbonate. Wide angle X-ray diffraction (WAXD) and transmission electron microscopy (TEM) indicated that exfoliated polycarbonate/clay nanocomposites could be obtained using organoclays which have reactive bisphenol functionality in the modifier. The glass transition temperature (T(g)) of the nanocomposites was studied using differential scanning calorimetry (DSC). The use of a more thermally stable modifier did not improve the color in polycarbonate clay nanocomposites. Although an approach to produce fully exfoliated PC nanocomposites are evident from this study, the process is far from perfect From the point of producing a color free transparent PC.